Enlarged Optic Nerve Sheath in Aneurysmal Subarachnoid Hemorrhage despite Normal Intracranial Pressure. Issue 2 (17th August 2015) - Bäuerle, Jochen; Niesen, Wolf‐Dirk; Egger, Karl; Buttler, Klaus‐Jürgen; Reinhard, Matthias
ABSTRACT: INTRODUCTION: This study investigates the diagnostic value of optic nerve sheath diameter (ONSD) assessed by transorbital sonography for estimation of intracranial pressure (ICP) in patients with aneurysmal subarachnoid hemorrhage (SAH). METHODS: Simultaneous measurements of the ONSD and ICP in 27 patients suffering from SAH and acute hydrocephalus after placement of an extraventricular drain. RESULTS: Despite normal mean ICP values ONSD was significantly higher in patients with SAH compared with healthy volunteers and no relevant decline of ONSD over time could be identified. In addition, no correlation between ONSD and ICP was observed. CONCLUSIONS: In patients with SAH and acute hydrocephalus after aneurysm rupture, the ONSD remains expanded after normalization of ICP. This is most likely due to an impaired retraction capability of the optic nerve sheath. This finding should be considered when using transorbital sonography in the neuromonitoring of aneurysmal SAH.